LL-37 stimulates the functions of adipose-derived stromal/stem cells via early growth response 1 and the MAPK pathway - Yang, Yoolhee (Stem Cell Res Ther, 2016)
BACKGROUND: LL-37 is a naturally occurring antimicrobial peptide found in the wound bed and assists wound repair. No published study has characterized the role of LL-37 in the function(s) of human mesenchymal stem cells (MSCs). This study investigated the functions of adipose-derived stromal/stem cells (ASCs) activated by LL-37 by performing both in vitro assays with cultured cells and in vivo assays with C57BL/6 mice with hair loss. METHODS: Human ASCs were isolated from healthy donors with written informed consent. To examine the effects of LL-37 on ASC function, cell proliferation and migration were measured by a cell counting kit (CCK-8) and a Transwell migration assay. Early growth response 1 (EGR1) mRNA expression was determined by microarray and real-time PCR analyses. The protein levels of EGR1 and regenerative factors were analyzed by specific enzyme-linked immunosorbent assays and western blotting. RESULTS: LL-37 treatment enhanced the proliferation and migration of human ASCs expressing formyl peptide receptor like-1. Microarray and real-time PCR data showed that EGR1 expression was rapidly and significantly increased by LL-37 treatment. LL-37 treatment also enhanced the production of EGR1. Moreover, small interfering RNA-mediated knockdown of EGR1 inhibited LL-37-enhanced ASC proliferation and migration. Activation of mitogen-activated protein kinases (MAPKs) was essential not only for LL-37-enhanced ASC proliferation and migration but also EGR1 expression; treatment with a specific inhibitor of extracellular signal-regulated kinase, p38, or c-Jun N-terminal kinase blocked the stimulatory effect of LL-37. EGR1 has a strong paracrine capability and can influence angiogenic factors in ASCs; therefore, we evaluated the secretion levels of vascular endothelial growth factor, thymosin beta-4, monocyte chemoattractant protein-1, and stromal cell-derived factor-1. LL-37 treatment increased the secretion of these regenerative factors. Moreover, treatment with the conditioned medium of ASCs pre-activated with LL-37 strongly promoted hair growth in vivo. CONCLUSIONS: These findings show that LL-37 increases EGR1 expression and MAPK activation, and that preconditioning of ASCs with LL-37 has a strong potential to promote hair growth in vivo. This study correlates LL-37 with MSC functions (specifically those of ASCs), including cell expansion, cell migration, and paracrine actions, which may be useful in terms of implantation for tissue regeneration. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13287-016-0313-4) contains supplementary material, which is available to authorized users.